A spraying composition and silver-aluminum transfer card prepared therefrom
Through the combination and modification technology of the spray composition, the problem that existing packaging papers require aluminum plating to achieve flash effect is solved, and silver aluminum transfer card without aluminum plating is realized. It has high flexibility, good adhesion and good temperature and solvent resistance, which promotes environmental protection.
Patent Information
- Application Number
- CN202411335474.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-09-24
- Publication Date
- 2025-04-15
- Estimated Expiration
- 2044-09-24
AI Technical Summary
Existing packaging paper requires aluminum plating to achieve flashing effect, the process is complex and the PET film is not easy to recycle, which affects environmental protection.
The spray composition, including aqueous polyurethane resin, aqueous epoxy resin, aqueous chlorine acetic resin and modified graphene oxide, is used to form a composite coating with high flexibility and good adhesion through compounding and modification technology, to achieve bending resistance, temperature and solvent resistance of the silver aluminum transfer card.
A silver aluminum transfer card that can form twill and flash on the surface of the packaging paper without aluminum plating is realized, which simplifies the process, improves the material's bending resistance, temperature and solvent resistance, and promotes environmental protection.
Smart Images

Figure BDA0005058127480000111 
Figure BDA0005058127480000121
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of silver-aluminum transfer cards, and in particular relates to a spraying composition and a silver-aluminum transfer card prepared therefrom. Background Art
[0002] Silver aluminum transfer card is widely used in the packaging paper industry because of its good printing adaptability, flatness and metallic luster. In particular, high-weight aluminum-sprayed transfer paper is mainly used in high-end brand packaging, especially various cosmetic boxes, wine boxes and cigarette boxes.
[0003] At present, if packaging cardboard needs to have a flashing effect, it is necessary to plate aluminum on the surface of the cardboard, and the process is relatively complicated. For example: Chinese patent 201510839965.4 discloses a transfer aluminum foil cardboard for cigarettes and its production method and equipment, the steps are: bonding transfer layer coating on PET film; vacuum plating aluminum on the transfer layer coating; coating transfer glue on the aluminum-plated surface of the PET matte silver transfer film; pressing the PET matte silver transfer film with the white cardboard; peeling off the PET film from the composite cardboard. The PET film of this method is not easy to separate from the paper, difficult to recycle and reuse, and not easy to decompose, which is not conducive to environmental protection.
[0004] Therefore, there is an urgent need for a silver aluminum transfer card that does not require aluminum plating, has a simple process, and can form twill and flashing effects on the surface of packaging card paper. Summary of the invention
[0005] The purpose of the invention is to provide a spray coating composition and a silver-aluminum transfer card prepared therefrom.
[0006] In order to achieve the above object, the present invention provides the following technical solutions:
[0007] A spraying composition, comprising the following raw materials in parts by weight: 8-13 parts of waterborne polyurethane resin, 4-9 parts of waterborne epoxy resin, 2-7 parts of waterborne chloroacetic acid resin, 3-7 parts of modified graphene oxide, 0.2-0.4 parts of leveling agent, 0.1-0.3 parts of waterborne adhesion promoter, and 75-80 parts of deionized water;
[0008] The preparation method of waterborne polyurethane resin is as follows: by weight:
[0009] (1) 18-22 parts of double-terminated amino polydimethylsiloxane, 50-55 parts of poly(1,4-butylene adipate), and 25-30 parts of hexamethylene diisocyanate are mixed, stirred and heated to 70-80° C., reacted for 2-3 hours, cooled to 40-45° C., 12-15 parts of dimethylol propionic acid, 7-10 parts of heterocyclic diol, and 55-60 parts of acetone are added, stirred and heated to 80-85° C., reacted for 4-5 hours, cooled to 40-45° C., 4-6 parts of triethylamine are added, reacted for 5-10 minutes, and then 2-5 parts of sodium ethylenediamine sulfonate are added, and the reaction time is 15-20 minutes to obtain a prepolymer;
[0010] (2) Add 270-300 parts of water to the prepolymer at 40-45° C. while stirring, continue stirring for 10-15 minutes, then add 3-5 parts of ethylenediamine, stir for 30-40 minutes, remove acetone, and prepare a waterborne polyurethane resin.
[0011] Furthermore, the average weight average molecular weight of the dual-terminated amino polydimethylsiloxane is 3000-4000 Da.
[0012] Furthermore, the average weight average molecular weight of poly(1,4-butylene adipate) is 3000-4000 Da.
[0013] Furthermore, the heterocyclic diol is 2,3,5,6-tetramethyl-1,4-dioxacyclo-2,5-diol.
[0014] The bending resistance of the silver-aluminum transfer card is not ideal when polyurethane coating and silver powder are mixed and directly coated on the adhesive layer. The present invention compounds water-based polyurethane resin, water-based epoxy resin and water-based chlorovinyl resin to improve the bending resistance of the silver-aluminum transfer card. After mixing water-based polyurethane resin, water-based epoxy resin and water-based chlorovinyl resin, a composite coating with high flexibility and good adhesion can be formed, thereby improving its bending resistance. Simultaneously using the homemade water-based polyurethane resin of the present invention and water-based epoxy resin and water-based chlorovinyl resin with specific parameters, the peeling performance of the silver-aluminum transfer card can also be improved. However, the temperature resistance of the silver-aluminum transfer card after compounding the three water-based resins is not ideal.
[0015] Furthermore, the preparation method of modified graphene oxide is:
[0016] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.14-0.16 parts by mass of graphene oxide were mixed, ultrasonicated for 30-40 minutes, 60-70 parts by mass of N,N-dimethylformamide were added, stirred at 100-105° C. for 3-4 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;
[0017] (2) 10 parts by weight of modified graphene oxide and 70-80 parts by weight of ethanol are mixed, and then 50-60 parts by weight of an aqueous solution of carboxylated polystyrene microspheres are added dropwise, stirred at 60-65° C. for 2-3 hours, centrifuged, and freeze-dried to obtain modified graphene oxide.
[0018] Graphene oxide has good heat resistance and can improve the thermal stability of the coating, but the dispersibility of graphene oxide in the system of the present invention is not good. The present invention can improve the temperature resistance of the silver-aluminum transfer card by adding modified graphene oxide to the spray composition. Carboxylated polystyrene microspheres are grafted on the surface of graphene oxide. Carboxylation can improve the compatibility with the polymer matrix, promote better interface bonding, and significantly improve the dispersibility of graphene oxide in the system of the present invention. The dispersibility of water-based polyurethane resin, water-based epoxy resin, and water-based chlorovinyl resin is better, forming a more complex network structure and enhancing the temperature resistance of the coating. At the same time, the addition of modified graphene oxide improves the solvent resistance of the silver-aluminum transfer card. Carboxylated polystyrene microspheres can chemically interact with the active groups in the water-based resin, enhance the bonding between the interfaces, and thus improve the resistance of the coating to solvents.
[0019] Furthermore, the graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and is purchased from Xianfeng Nano.
[0020] Furthermore, the particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %. Furthermore, the epoxy equivalent of the waterborne epoxy resin is 210-230 g / mol. Brand: Phoenix WSR 6101 epoxy resin.
[0021] Furthermore, the glass transition temperature of the water-based chlorovinyl resin is 79±1°C, and the viscosity is 160-180mPa·s. Brand: American Dow water-based chlorovinyl resin AW-875.
[0022] Furthermore, the leveling agent is selected from one or more of BYK300, BYK306, and BYK333.
[0023] Furthermore, the water-based adhesion promoter is E-Tide GT-2000.
[0024] The present invention also provides a silver aluminum transfer card prepared by using the spray composition, and the preparation method is: coating one surface of the white card paper with water-based glue, and the wet coating amount of the water-based glue is 5-10g / m 2 , apply paint on the water-based glue layer, the dry coating amount of the paint is 1.6-1.8g / m 2 The coating is a mixture of the spray composition and silver powder in a weight ratio of 1-3:1; the coating is dried at a heating temperature of 90-100°C for 5-10s.
[0025] Furthermore, the white cardboard is made of all wood pulp fibers, the surface roughness of the white cardboard is ≤1.5 using the PPS method (um), and the paper weight per unit area is 150-200g / m 2 .
[0026] Water-based glue was purchased from Shandong Jiade Packaging Materials Co., Ltd., model PJ-221.
[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:
[0028] 1. The present invention compounds waterborne polyurethane resin, waterborne epoxy resin and waterborne chlorovinyl resin to improve the bending resistance of the silver-aluminum transfer card. After the waterborne polyurethane resin, waterborne epoxy resin and waterborne chlorovinyl resin are mixed, a composite coating with high flexibility and good adhesion can be formed, thereby improving its bending resistance. Simultaneously using the self-made waterborne polyurethane resin of the present invention and the waterborne epoxy resin and waterborne chlorovinyl resin with specific parameters can also improve the peeling performance of the silver-aluminum transfer card.
[0029] 2. The present invention can improve the temperature resistance of the silver-aluminum transfer card by adding modified graphene oxide to the spray composition. Carboxylated polystyrene microspheres are grafted on the surface of graphene oxide. Carboxylation can improve the compatibility with the polymer matrix, promote better interface bonding, and significantly improve the dispersibility of graphene oxide in the system of the present invention. At the same time, the addition of modified graphene oxide improves the solvent resistance of the silver-aluminum transfer card. Carboxylated polystyrene microspheres can chemically interact with the active groups in the water-based resin, enhance the bonding between the interfaces, and thus improve the resistance of the coating to solvents.
[0030] 3. The present invention provides mesh holes inclined at 45° on the smoothing roller, so that the silver powder coated on the packaging cardboard can stand on the packaging cardboard at an angle, presenting a flashing effect, and forming diagonal lines on the packaging cardboard. While the smoothing roller is coating one side of the packaging cardboard, the steel pipe is used to press the other side of the packaging cardboard. The smoothing roller and the steel pipe jointly press the packaging cardboard, so that the quality is stable and the coating is uniform. DETAILED DESCRIPTION
[0031] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0032] Example 1
[0033] This embodiment provides a spraying composition, comprising the following raw materials in parts by weight: 10 parts of waterborne polyurethane resin, 6 parts of waterborne epoxy resin, 5 parts of waterborne chlorovinyl resin, 5 parts of modified graphene oxide, 0.3 parts of leveling agent, 0.2 parts of waterborne adhesion promoter, and 78 parts of deionized water;
[0034] The preparation method of waterborne polyurethane resin is as follows: by weight:
[0035] (1) 20 parts of double-terminated amino polydimethylsiloxane, 52 parts of poly(1,4-butylene adipate), and 28 parts of hexamethylene diisocyanate were mixed, stirred and heated to 75° C., reacted for 2.6 hours, cooled to 42° C., 13 parts of dihydroxymethyl propionic acid, 8 parts of heterocyclic diol, and 58 parts of acetone were added, stirred and heated to 82° C., reacted for 4.6 hours, cooled to 42° C., 5 parts of triethylamine were added, reacted for 8 minutes, and then 4 parts of sodium ethylenediamine sulfonate were added, and the reaction time was 17 minutes to obtain a prepolymer;
[0036] (2) At 43° C., 280 parts of water were added to the prepolymer under stirring, and the stirring was continued for 12 minutes. Then, 4 parts of ethylenediamine were added and stirred for 35 minutes. The acetone was removed to obtain a waterborne polyurethane resin.
[0037] The average weight average molecular weight of poly(1,4-butylene adipate) is 3500 Da and it was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with a hydroxyl value of 60 mgKOH / g.
[0038] The heterocyclic diol is 2,3,5,6-tetramethyl-1,4-dioxacyclic-2,5-diol.
[0039] The average weight average molecular weight of double-terminated amino polydimethylsiloxane was 3000 Da and was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0040] The preparation method of modified graphene oxide is:
[0041] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.15 parts by mass of graphene oxide were mixed, ultrasonicated for 35 minutes, 65 parts by mass of N,N-dimethylformamide were added, stirred at 102° C. for 3.4 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;
[0042] (2) 10 parts by weight of modified graphene oxide and 75 parts by weight of ethanol were mixed, and then 56 parts by weight of an aqueous solution of carboxylated polystyrene microspheres were added dropwise, stirred at 62° C. for 2.7 h, centrifuged, and freeze-dried to obtain modified graphene oxide.
[0043] The graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and was purchased from Xianfeng Nano.
[0044] The carboxylated polystyrene microspheres in the aqueous solution had a particle size of 20 nm and a solid content of 2.5 wt %, purchased from Xianfeng Nano, item number: 103392.
[0045] The epoxy equivalent of waterborne epoxy resin is 210-230g / mol. Brand: Phoenix WSR 6101 epoxy resin.
[0046] The glass transition temperature of water-based chlorovinyl resin is 79±1℃, and the viscosity is 160-180mPa·s. Brand: American Dow water-based chlorovinyl resin AW-875.
[0047] The leveling agent is BYK300.
[0048] The water-based adhesion promoter is Yitai GT-2000.
[0049] The silver aluminum transfer card prepared by using the spray composition is prepared by coating one surface of the white card paper with water-based glue, and the wet coating amount of the water-based glue is 8g / m 2 , apply paint on the water-based glue layer, the dry coating amount of the paint is 1.7g / m 2 The coating is a mixture of the spray composition and silver powder in a weight ratio of 2:1; the coating is dried at a heating temperature of 95°C for 8 seconds.
[0050] White cardboard is made of pure wood pulp fiber. The surface roughness of white cardboard is ≤1.5 using the PPS method (um). The paper weight per unit area is 180g / m 2 The water-based glue was purchased from Shandong Jiade Packaging Materials Co., Ltd., model PJ-221.
[0051] Example 2
[0052] This embodiment provides a spray composition, comprising the following raw materials in parts by weight: 8 parts of waterborne polyurethane resin, 4 parts of waterborne epoxy resin, 2 parts of waterborne chlorovinyl resin, 3 parts of modified graphene oxide, 0.2 parts of leveling agent, 0.1 parts of waterborne adhesion promoter, and 75 parts of deionized water;
[0053] The preparation method of waterborne polyurethane resin is as follows: by weight:
[0054] (1) 18 parts of double-terminated amino polydimethylsiloxane, 50 parts of poly(1,4-butylene adipate), and 25 parts of hexamethylene diisocyanate were mixed, stirred and heated to 70° C., reacted for 2 hours, cooled to 40° C., and continued to add 12 parts of dihydroxymethyl propionic acid, 7 parts of heterocyclic diols, and 55 parts of acetone, stirred and heated to 80° C., reacted for 4 hours, cooled to 40° C., added 4 parts of triethylamine, reacted for 5 minutes, and then added 2 parts of sodium ethylenediamine sulfonate, reacted for 15 minutes, to obtain a prepolymer;
[0055] (2) At 40° C., 270 parts of water were added to the prepolymer under stirring, and the stirring was continued for 10 minutes. Then, 3 parts of ethylenediamine were added and stirred for 30 minutes. The acetone was removed to obtain a waterborne polyurethane resin.
[0056] The average weight average molecular weight of poly(1,4-butylene adipate) is 3500. It was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with a hydroxyl value of 60 mgKOH / g.
[0057] The heterocyclic diol is 2,3,5,6-tetramethyl-1,4-dioxacyclic-2,5-diol.
[0058] The average weight average molecular weight of double-terminated amino polydimethylsiloxane is 3000. It was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0059] The preparation method of modified graphene oxide is:
[0060] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.14 parts by mass of graphene oxide were mixed, ultrasonicated for 30 minutes, 60 parts by mass of N,N-dimethylformamide were added, stirred at 100° C. for 3 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;
[0061] (2) 10 parts by weight of modified graphene oxide and 70 parts by weight of ethanol were mixed, and then 50 parts by weight of an aqueous solution of carboxylated polystyrene microspheres were added dropwise, stirred at 60° C. for 2 h, centrifuged, and freeze-dried to obtain modified graphene oxide.
[0062] The graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and was purchased from Xianfeng Nano.
[0063] The particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt%. The epoxy equivalent of the waterborne epoxy resin is 210-230 g / mol. Brand: Phoenix WSR 6101 epoxy resin.
[0064] The glass transition temperature of water-based chlorovinyl resin is 79±1℃, and the viscosity is 160-180mPa·s. Brand: American Dow water-based chlorovinyl resin AW-875.
[0065] The leveling agent is BYK306.
[0066] The water-based adhesion promoter is Yitai GT-2000.
[0067] The silver aluminum transfer card prepared by using the spray composition is prepared by coating one surface of the white card paper with water-based glue, and the wet coating amount of the water-based glue is 8g / m 2, apply paint on the water-based glue layer, the dry coating amount of the paint is 1.7g / m 2 The coating is a mixture of the spray composition and silver powder in a weight ratio of 2:1; the coating is dried at a heating temperature of 95°C for 8 seconds.
[0068] White cardboard is made of pure wood pulp fiber. The surface roughness of white cardboard is ≤1.5 using the PPS method (um). The paper weight per unit area is 180g / m 2 The water-based glue was purchased from Shandong Jiade Packaging Materials Co., Ltd., model PJ-221.
[0069] Example 3
[0070] This embodiment provides a spraying composition, comprising the following raw materials in parts by weight: 13 parts of waterborne polyurethane resin, 9 parts of waterborne epoxy resin, 7 parts of waterborne chlorovinyl resin, 7 parts of modified graphene oxide, 0.4 parts of leveling agent, 0.3 parts of waterborne adhesion promoter, and 80 parts of deionized water;
[0071] The preparation method of waterborne polyurethane resin is as follows: by weight:
[0072] (1) 22 parts of double-terminated amino polydimethylsiloxane, 55 parts of poly(1,4-butylene adipate), and 30 parts of hexamethylene diisocyanate were mixed, stirred and heated to 80° C., reacted for 3 hours, cooled to 45° C., 15 parts of dihydroxymethyl propionic acid, 10 parts of heterocyclic diol, and 60 parts of acetone were added, stirred and heated to 85° C., reacted for 5 hours, cooled to 45° C., 6 parts of triethylamine were added, reacted for 10 minutes, and then 5 parts of sodium ethylenediamine sulfonate were added, and the reaction time was 20 minutes to obtain a prepolymer;
[0073] (2) At 45° C., 300 parts of water were added to the prepolymer under stirring, and the stirring was continued for 15 minutes. Then, 5 parts of ethylenediamine were added and stirred for 40 minutes. The acetone was removed to obtain a waterborne polyurethane resin.
[0074] The average weight average molecular weight of poly(1,4-butylene adipate) is 3500. It was purchased from Wuhan Huaxiang Kejie Biotechnology Co., Ltd., with a hydroxyl value of 60 mgKOH / g.
[0075] The heterocyclic diol is 2,3,5,6-tetramethyl-1,4-dioxacyclic-2,5-diol.
[0076] The average weight average molecular weight of double-terminated amino polydimethylsiloxane is 3000. It was purchased from Xi'an Qiyue Biotechnology Co., Ltd.
[0077] The preparation method of modified graphene oxide is:
[0078] (1) Under a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.16 parts by mass of graphene oxide were mixed, ultrasonicated for 40 minutes, 70 parts by mass of N,N-dimethylformamide were added, stirred at 105° C. for 4 hours, centrifuged, and freeze-dried to obtain modified graphene oxide;
[0079] (2) 10 parts by weight of modified graphene oxide and 80 parts by weight of ethanol were mixed, and then 60 parts by weight of an aqueous solution of carboxylated polystyrene microspheres were added dropwise, stirred at 65° C. for 3 h, centrifuged, and freeze-dried to obtain modified graphene oxide.
[0080] The graphene oxide has a sheet diameter of 0.5-5 μm and a thickness of 0.8-1.2 nm and was purchased from Xianfeng Nano.
[0081] The particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt%. The epoxy equivalent of the waterborne epoxy resin is 210-230 g / mol. Brand: Phoenix WSR 6101 epoxy resin.
[0082] The glass transition temperature of water-based chlorovinyl resin is 79±1℃, and the viscosity is 160-180mPa·s. Brand: American Dow water-based chlorovinyl resin AW-875.
[0083] The leveling agent is BYK333.
[0084] The water-based adhesion promoter is Yitai GT-2000.
[0085] The silver aluminum transfer card prepared by using the spray composition is prepared by coating one surface of the white card paper with water-based glue, and the wet coating amount of the water-based glue is 8g / m 2 , apply paint on the water-based glue layer, the dry coating amount of the paint is 1.7g / m 2 The coating is a mixture of the spray composition and silver powder in a weight ratio of 2:1; the coating is dried at a heating temperature of 95°C for 8 seconds.
[0086] White cardboard is made of pure wood pulp fiber. The surface roughness of white cardboard is ≤1.5 using the PPS method (um). The paper weight per unit area is 180g / m 2 The water-based glue was purchased from Shandong Jiade Packaging Materials Co., Ltd., model PJ-221.
[0087] Comparative Example 1
[0088] The difference between this comparative example and Example 1 is: 6 parts of waterborne polyurethane resin, 2 parts of waterborne epoxy resin, and 13 parts of waterborne chloroacetic acid resin.
[0089] Comparative Example 2
[0090] The difference between this comparative example and Example 1 is that the waterborne polyurethane resin is a commercially available product. Brand: Toyobo, MD-1480, hydroxyl value 6KOHmg / g.
[0091] Comparative Example 3
[0092] The difference between this comparative example and Example 1 is that the sheet diameter of graphene oxide is 10-20 μm and the thickness is 1.2-1.5 nm. It was purchased from Shanghai Xiangtian Nanomaterial Co., Ltd.
[0093] Comparative Example 4
[0094] The difference between this comparative example and Example 1 is that the carboxylated polystyrene microsphere aqueous solution is replaced with a nano-titanium dioxide aqueous solution, the nano-titanium dioxide content in the nano-titanium dioxide aqueous solution is 2.5wt%, and the average particle size of the nano-titanium dioxide is 20nm.
[0095] The difference between this comparative example and Example 1 is that the glass transition temperature of the water-based chlorovinyl resin is 63° C. and the viscosity is 300 mPa·s. Brand: Nissin water-based chlorovinyl resin, Vinyblan 603.
[0096] Comparative Example 6
[0097] The difference between this comparative example and Example 1 is that the epoxy equivalent of the waterborne epoxy resin is 176-184 g / mol. Phoenix brand E54 epoxy resin.
[0098] Performance Testing
[0099] The performance tests were performed on the silver-aluminum transfer cards prepared in Examples 1-3 and Comparative Examples 1-6.
[0100] Peeling performance test method: Use 3M tape to quickly peel it off at a 45° angle. The peeling must be clean and there must be no residual adhesive.
[0101] Temperature resistance test method: Use a heat sealer at a fixed pressure of 500kPa and a time of 1s to directly press the silver aluminum transfer card. The temperature at which deformation is visible to the naked eye is taken as the maximum temperature that the coating can withstand.
[0102] Solvent resistance test method: Use a cotton swab dipped in ethanol to wipe back and forth on the silver aluminum transfer card. Wipe back and forth as one time until the coating is damaged. Record the number of times the coating can withstand alcohol wiping.
[0103] Bending resistance test method: bend the silver aluminum transfer card back and forth until the coating layer is damaged, and record the number of bends.
[0104] Table 1 Test results
[0105]
[0106]
[0107] It can be seen from the above performance test results that the silver-aluminum transfer cards of Examples 1-3 have excellent comprehensive performance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of the components in the system.
[0108] However, since the necessary technical solutions were not adopted in the comparative examples, the corresponding performance tests were significantly worse than those of the embodiments. In comparative example 1, the waterborne polyurethane resin, waterborne epoxy resin and waterborne chlorovinyl resin were changed, and it can be seen that the bending resistance effect decreased, proving that the bending resistance compounding solution has an important influence on the bending resistance effect. The modified graphene oxide solution was not used in comparative examples 3-4, and it can be seen from the results that the temperature resistance was affected. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.
[0109] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.
Claims
1. A spray composition, characterized in that The invention comprises the following raw materials in parts by weight: 8-13 parts of waterborne polyurethane resin, 4-9 parts of waterborne epoxy resin, 2-7 parts of waterborne chloroacetic acid resin, 3-7 parts of modified graphene oxide, 0.2-0.4 parts of leveling agent, 0.1-0.3 parts of waterborne adhesion promoter, and 75-80 parts of deionized water; The preparation method of waterborne polyurethane resin is as follows: (1) 18-22 parts of double-terminated amino polydimethylsiloxane, 50-55 parts of poly(1,4-butylene adipate) and 25-30 parts of hexamethylene diisocyanate are mixed, stirred and heated to 70-80°C, reacted for 2-3 hours, cooled to 40-45°C, and continued to add 12-15 parts of dimethylol propionic acid, 7-10 parts of heterocyclic diol and 55-60 parts of acetone, stirred and heated to 80-80°C. 5°C for 4-5 hours, cool to 40-45°C, add 4-6 parts of triethylamine, react for 5-10 minutes, then add 2-5 parts of sodium ethylenediamine sulfonate, react for 15-20 minutes to obtain a prepolymer; (2) add 270-300 parts of water to the prepolymer at 40-45°C under stirring, continue stirring for 10-15 minutes, then add 3-5 parts of ethylenediamine, stir for 30-40 minutes, remove acetone, and obtain a waterborne polyurethane resin; The preparation method of modified graphene oxide is as follows: (1) in a nitrogen atmosphere, 1 part by mass of 3-isocyanatepropyltrimethoxysilane and 0.14-0.16 parts by mass of graphene oxide are mixed, ultrasonicated for 30-40 minutes, 60-70 parts by mass of N,N-dimethylformamide are added, stirred at 100-105° C. for 3-4 hours, centrifuged, and freeze-dried to obtain a modified graphene oxide intermediate; (2) 10 parts by mass of the modified graphene oxide intermediate and 70-80 parts by mass of ethanol are mixed, and then 50-60 parts by mass of a carboxylated polystyrene microsphere aqueous solution are added dropwise, stirred at 60-65° C. for 2-3 hours, centrifuged, and freeze-dried to obtain the modified graphene oxide.
2. The spray composition according to claim 1, characterized in that The average weight average molecular weight of the dual-terminated amino polydimethylsiloxane is 3000-4000 Da.
3. The spray composition according to claim 1, characterized in that The average weight average molecular weight of poly(1,4-butylene adipate) is 3000-4000 Da.
4. The spray composition according to claim 1, characterized in that The sheet diameter of graphene oxide is 0.5~5μm and the thickness is 0.8-1.2nm.
5. The spray composition according to claim 1, characterized in that The particle size of the carboxylated polystyrene microspheres in the carboxylated polystyrene microsphere aqueous solution is 20 nm, and the solid content is 2.5 wt %.
6. The spray composition according to claim 1, characterized in that The epoxy equivalent of waterborne epoxy resin is 210-230g / mol.
7. The spray composition according to claim 1, characterized in that The glass transition temperature of water-based chlorovinyl resin is 79±1℃ and the viscosity is 160-180 mPa·s.
8. The spray composition according to claim 1, characterized in that The leveling agent is selected from one or more of BYK300, BYK306 and BYK333.
9. A silver-aluminum transfer card prepared using the spray composition according to any one of claims 1 to 8, characterized in that: The preparation method of the silver aluminum transfer card is as follows: apply water-based glue on one surface of the white card paper, and the wet coating amount of the water-based glue is 5-10g / m 2 , apply paint on the water-based glue layer, the dry coating amount of the paint is 1.6-1.8g / m 2 The coating is a mixture of the spray composition and silver powder in a weight ratio of 1-3:1; the coating is dried at a heating temperature of 90-100°C for 5-10s.
Citation Information
Patent Citations
Tobacco transferring aluminum foil paperboard as well as producing method and equipment of tobacco transferring aluminum foil paperboard
CN105386368A
Environment-friendly type moldable aqueous transfer coating, preparation and use thereof
CN101407656A
Aqueous laser aluminizing transferring coating and preparation method thereof
CN108624216A
High-temperature-resistant functionalized graphene modified waterborne polyurethane as well as preparation method and application thereof
CN112812252A
Water-based flexographic printing ink suitable for lamination paperboard
CN116200071A